Oncologic emergencies: nursing care proposed in literature - Suelem Cristina Pignatari; Renata Cristina Campos Pereira Silveira; Emília Campos Carvalho (Online Brazilian Journal of Nursing, 2008)
Introduction: Cancer patients need special care which improve their quality of life and protect them from complications. Nevertheless, it is not always possible to prevent undesired events, thus knowledge on oncologic emergencies is needed for fast interventions that can save lives. Objectives: To identify the knowledge about nursing care in oncologic emergencies and present nursing interventions mentioned for these situations. Method: Integrative literature review, using LILACS and PubMed databases for the search of articles, 30 of them were selected. Results: Among the articles’ authors, 56,7% are nurses and 40% of the journals are nursing journals. Knowledge and interventions in nursing appeared in only 26,7% of the articles, however, were described in a detailed way and valuing comprehensive care to patient.